Pengaruh Motivasi Terhadap Kepuasan Kerja Pegawai pada Kantor Dinas Peternakan dan Perikanan Kabupaten Sidenreng Rappang - Herman Dema; Rahmawati M (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2012)
Country civic-duty employee (what we call Pegawai Negeri Sipil) isa form of human resources which deserved attention for the role ofcivic worker doing whatever it takes to run a country, and beingresponsible for the successful development in this country. Withnational policy called legislation #32 in 2004 about theimplementation of regional autonomy based on decentralization, The Department of Agriculture and Fishery in Sidenreng Rappangregency as one of regional government should be capable of publicservicing to the people.This research is to determine the employee's motivation and whetherit effects their job satisfaction at The department of Agriculture andFishery office in Sidenreng Rappang regency.The samples in this research are taken from all employee as thepopulation of The Department of Agriculture and Fishery office,which are forty-four (44) people. The data collecting methods arequestionaire, observation, and literature study. The data analysismethods are coefficient of correlation, and the method used to seewhether there's influences from motivation to job satisfaction inpercentage is coefficient of determination.The result shows that employee's motivation is in good rate,averaging 3,70 represents good category. The statistical result usingcoefficient of correlation analysis shows that job satisfaction isindeed affected by motivation by a positive +0,262 of correlationcoefficient, and 7% percentage by using determination coeeficient. The hypothetical test is also resulting 1,761 being greater than1,68195, means that the hypothetic is accepted, there is indeedinfluences between employee's motivation and employee's jobsatisfaction at The Department of Agriculture and Fishery inSidenreng Rappang regency.